Avian Leucosis Virus-Host Interaction: The Involvement of Host Factors in Viral Replication - Tang, Shuang; Li, Jie; Chang, Yung-Fu; Lin, Wencheng (Frontiers in Immunology, 2022)
Avian leukosis virus (ALV) causes various diseases associated with tumor formation and decreased fertility. Moreover, ALV induces severe immunosuppression, increasing susceptibility to other microbial infections and the risk of failure in subsequent vaccination against other diseases. There is growing evidence showing the interaction between ALV and the host. In this review, we will surveying the present knowledge of the involvement of host factors in the important molecular events during ALV infection, and discussing the futuristic perspectives in this angle.